Broadband printed sectorized coverage antennas for millimeter-wave wireless applications. - Waterhouse, R.B (IEEE Transactions on antennas and propagation)
We present a simple method to reduce the back radiation of broadband millimeter-wave printed antenna arrays. By utilizing specially designed reflector patches, the front-to-back ratio of an array of aperture stacked patches can be improved to greater than 30 dB across the entire 26-40 GHz frequency band, making this form of antenna array suitable for sectorized coverage local-multipoint-distribution service (LMDS) and picocellular mobile networks